CONTENT ANALYSIS OF YOUTUBE VIDEOS AND COMPATIBILITY TO K-13 CURRICULUM OF THE 7TH-GRADE STUDENT (A Descriptive Study on the YouTube Channel 'Miss Nita') - Prana, Ryan Sevtio; Bunau, Eusabinus; Salam, Urai (Universitas Tanjungpura, 2022)
'Miss Nita